2018
DOI: 10.1088/1741-4326/aab30a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pedestal fluctuation on ELM frequency in the EAST tokamak

Abstract: The dependence of ELM frequency on heating power has been studied on the Experimental Advanced Superconducting Tokamak (EAST). It is found that the ELM frequency (f ELM ) generally increases with the power through separatrix (P sep ), indicating type-I ELM in these plasmas. However, there are two data points, named 'abnormal ELM' in the present paper, which have much lower f ELM than the 'normal ELM', while both types of ELM have similar ELM energy losses. The 'abnormal ELM' occurs at a phase with increased ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In addition, the dependence of poloidal width on the ELM amplitude is investigated, and about 100 ELM-induced filaments are used for statistics. In the statistical process, there are different definitions of the ELM amplitude in the literature [26]. In this work, ELM amplitude is defined as the energy loss, i.e.…”
Section: Dependence Of Filament Characteristics On Plasma Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the dependence of poloidal width on the ELM amplitude is investigated, and about 100 ELM-induced filaments are used for statistics. In the statistical process, there are different definitions of the ELM amplitude in the literature [26]. In this work, ELM amplitude is defined as the energy loss, i.e.…”
Section: Dependence Of Filament Characteristics On Plasma Parametersmentioning
confidence: 99%
“…i The end time, ( ) t i , end at which a D decreases to ( ) exp 3 of the peak value for the i th ELM burst, is also defined. For the calculation of W ELM [26], the energy loss due to the i th ELM, ( ) W i , ELM is calculated as the difference between the maximum value and the value of W MHD at ( ) t i end in a small time interval around the i th ELM event, i.e.…”
Section: Elmmentioning
confidence: 99%
“…show that a coherent mode (CM) [10] with frequency sweeping down appears in density and temperature (but not in magnetic) fluctuation spectra during the ELM-free phase before the first ELM. It has been shown that the CM is in the edge pedestal region and has a toroidal mode number n = 12-17 [10], with characteristics close to the resistive ballooning mode [34]. More characteristics of this mode have been presented in appendix B, including an argument of the mode rotation direction in the plasma frame.…”
Section: Figures 1(d)-(f )mentioning
confidence: 97%
“…In experiment, it has been found that several turbulence modes in the ELM-free phase or inter-ELM phase are closely related to the pedestal transport [10][11][12][13][14][15][16][17][18][19][20][21][22]. In simulation, gyrokinetic codes found that several types of micro-turbulence, such as the micro-tearing mode (MTM) [23,24] and electron temperature gradient (ETG) mode [25], could be responsible for the pedestal transport.…”
Section: Nuclear Fusionmentioning
confidence: 99%